TAK1 mediates excessive autophagy via p38 and ERK in cisplatin‐induced acute kidney injury. Issue 5 (5th March 2018) - Zhou, Jun; Fan, Youling; Zhong, Jiying; Huang, Zhenxing; Huang, Teng; Lin, Sen; Chen, Hongtao
Abstract: The ability of cisplatin (cis‐diamminedichloroplatinum II) toxicity to induce acute kidney injury (AKI) has attracted people's attention and concern for a long time, but its molecular mechanisms are still widely unknown. We found that the expression of transforming growth factor‐β (TGF‐β)‐activated kinase 1 (TAK1) could be increased in kidneys of mice administrated with cisplatin. Autophagy is an evolutionarily conserved catabolic pathway and is involved in various acute and chronic injuries. Moreover, p38 MAPK (mitogen‐activated protein kinase) and ERK regulate autophagy in response to various stimuli. Therefore, our hypothesis is that cisplatin activates TAK1, which phosphorylates p38 and ERK, leading to excessive autophagy of tubular epithelial cells and thus exacerbating kidney damage. Here, BALB/c mice were intraperitoneally injected with a TAK1 inhibitor and were then administrated with sham or cisplatin at 20 mg/kg by intraperitoneal injection. Compared with mice in the vehicle cisplatin group, mice intraperitoneally injected with a TAK1 inhibitor were found to have lower serum creatinine and less tubular damage following cisplatin‐induced AKI. Furthermore, inhibition of TAK1 reduced p38 and Erk phosphorylation, decreased expression of LC3II and reversed the down‐regulation of P62 expression induced by cisplatin. The hypothesis was verified with tubular epithelial cells administrated with cisplatin in vitro. Finally, p38 inhibitor or ERK inhibitor abated autophagy activation and cell viability reduction in tubular epithelial cells treated with cisplatin plus TAK1 overexpression vector. Taken together, our results show that cisplatin activates TAK1, which phosphorylates p38 and ERK, leading to excessive autophagy of tubular epithelial cells that exacerbates kidney damage.